Synergistic effect of protease and cranberry powder to enhance the quality characteristics of fried beef meatballs. Issue 1 (6th March 2023) - Liang, Xinyue; Zhou, Na; Irfan, Muhammad; Gerard, Mugabe; Wang, Yonghua; Wang, Fanghua
Abstract: Tenderness and color affect meat quality. Our previous results indicated that cranberry powder can partially replace NaNO2 in fried beef meatballs processing without compromising on its quality, especially the color. In this research, the effect of different protease enzymes combined with 10 g/kg cranberry powder for improving the quality, characteristics of fried beef meatballs were investigated. Addition of protease together with cranberry powder, the tenderness, a * value, and sensory score of fried beef meatballs were improved as a whole compared with sole 10 g/kg cranberry powder addition, indicating that protease had a beneficial effect on improving the quality of fried beef meatballs. Among the different proteases screened, the fried beef meatballs prepared with 80 U/g bromelain had a relatively higher a * value (13.06) and tenderness (12.61), and the overall acceptability (6) was the highest. Meanwhile, this combination exhibited lower shear stress and cooking loss, with higher water‐holding capacity and protein content. The effects of marination time on the physicochemical properties of fried beef meatballs were also investigated. Marinating for 8 h displayed the best effect with the highest a * value, the lowest shear force. The current study provides a potential solution for the quality improvement of fried beef meatballs. Abstract : In the present study, the effect of papain, bromelain, and ficin in different concentrations combined with 10 g/kg cranberry powder for improving the quality properties of fried beef meatballs were investigated, respectively. Different quality characteristics index, such as color, shearing force, texture, and protein solubility of fried beef balls were investigated and compared, and the best combination formula was acquired. The relationship between protease and cranberry powder was also discussed. The current study would provide more convincing evidence for recommending the addition of cranberry powder together with bromelain during fried beef meatballs processing to further improve its qualities.